Pathogenic Role of the Damage-Associated Molecular Patterns S100A8 and S100A9 in Coxsackievirus B3–Induced Myocarditis. (November 2017) - Müller, Irene; Vogl, Thomas; Pappritz, Kathleen; Miteva, Kapka; Savvatis, Konstantinos; Rohde, David; Most, Patrick; Lassner, Dirk; Pieske, Burkert; Kühl, Uwe; Van Linthout, Sophie; Tschöpe, Carsten
Abstract : Background: The alarmins S100A8 and S100A9 are damage-associated molecular patterns, which play a pivotal role in cardiovascular diseases, inflammation, and viral infections. We aimed to investigate their role in Coxsackievirus B3 (CVB3)–induced myocarditis. Methods and Results: S100A8 and S100A9 mRNA expression was 13.0-fold ( P =0.012) and 5.1-fold ( P =0.038) higher in endomyocardial biopsies from patients with CVB3-positive myocarditis compared with controls, respectively. Elimination of CVB3 led to a downregulation of these alarmins. CVB3-infected mice developed an impaired left ventricular function and displayed an increased left ventricular S100A8 and S100A9 protein expression versus controls. In contrast, CVB3-infected S100A9 knockout mice, which are also a complete knockout for S100A8 on protein level, showed an improved left ventricular function, which was associated with a reduced cardiac inflammatory and oxidative response, and lower CVB3 copy number compared with wild-type CVB3 mice. Exogenous application of S100A8 to S100A9 knockout CVB3 mice induced a severe myocarditis similar to wild-type CVB3 mice. In CVB3-infected HL-1 cells, S100A8 and S100A9 enhanced oxidative stress and CVB3 copy number compared with unstimulated infected cells. In CVB3-infected RAW macrophages, both alarmins increased MIP-2 (macrophage inflammatory protein-2) chemokine expression, which was reduced in CVB3 S100A8 knockdown versus scrambled siRNA CVB3 cells. Conclusions: S100A8 and S100A9 aggravate CVB3-induced myocarditis and might serve as therapeutic targets in inflammatory cardiomyopathies. Abstract : Supplemental Digital Content is available in the text.